Calpastatin-mediated inhibition of calpains in the mouse brain prevents mutant ataxin 3 proteolysis, nuclear localization and aggregation, relieving Machado–Joseph disease - Simões, Ana T. (2012)
Machado–Joseph disease is the most frequently found dominantly-inherited cerebellar ataxia. Over-repetition of a CAG trinucleotide in the MJD1 gene translates into a polyglutamine tract within the ataxin 3 protein, which upon proteolysis may trigger Machado–Joseph disease. We investigated the role of calpains in the generation of toxic ataxin 3 fragments and pathogenesis of Machado–Joseph disease. For this purpose, we inhibited calpain activity in mouse models of Machado–Joseph disease by overexpressing the endogenous calpain-inhibitor calpastatin. Calpain blockage reduced the size and number of mutant ataxin 3 inclusions, neuronal dysfunction and neurodegeneration. By reducing fragmentation of ataxin 3, calpastatin overexpression modified the subcellular localization of mutant ataxin 3 restraining the protein in the cytoplasm, reducing aggregation and nuclear toxicity and overcoming calpastatin depletion observed upon mutant ataxin 3 expression. Our findings are the first in vivo proof that mutant ataxin 3 proteolysis by calpains mediates its translocation to the nucleus, aggregation and toxicity and that inhibition of calpains may provide an effective therapy for Machado–Joseph disease.